Analisis Strategi Pemasaran Berbasis Konten Usaha Kecil dan Menengah di Media Sosial - Indah Winarni; Pasiska Pasiska (CV. Kalimasada Group, 2026)
Small and Medium Enterprises (SMEs) in Indonesia play a strategic role in the national economy, yet they still face various challenges in product marketing, particularly in the digital era. One approach deemed relevant to addressing these challenges is content-based marketing through social media. This study aims to analyze effective content-based marketing strategies for SMEs on social media. The study used a qualitative approach, using case studies and content analysis methods, on several SMEs actively utilizing social media as a marketing tool. The results indicate that the effectiveness of content-based marketing is determined by the creation of relevant and engaging content, the use of appropriate hashtags, active interaction with customers, and regular measurement and evaluation of content performance. The findings also indicate that utilizing social media can increase brand awareness, drive sales growth, and build long-term relationships with customers. This study provides theoretical contributions to the development of content-based digital marketing studies, as well as practical implications for SMEs in designing and managing effective marketing strategies through social media